Mining the Prognostic Value of HNRNPAB and Its Function in Breast Carcinoma - Yun Cao; Wei Zhang; Yi-Ting Jin; Qiang Zou (International Journal of Genomics)
Heterogeneous nuclear ribonucleoproteins (HNRNPs) are crucial members in the pathogenesis and progression of numerous cancers. However, the expression pattern and clinical significance of HNRNPs in breast carcinoma (BC) remain to be investigated. In the present study, bioinformatic analysis identified HNRNPAB as the only commonly upregulated HNRNP in BC. Elevated expression of HNRNPAB was positively associated with more aggressive diseases and poorer survival rates in BC. Pathway analysis revealed that HNRNPAB coexpressed genes were enriched in the pathway of G2/M phase transition, and the expression level of HNRNPAB was strongly correlated with those of CCNB1, CDK1, CDC25A, and CDC25C. Experiments in vitro demonstrated that HNRNPAB knockdown suppressed cell proliferation and blocked the G2/M phase transition in BC. Taken together, this study provides the initial evidence that HNRNPAB may be employed as an innovative therapeutic target as well as a prognostic biomarker in BC patients.